Divergent drivers of richness–depth gradients among taxonomic groups - Inbar Dahan; Shahar Chaikin; Lilach Raijman-Nagar; Erez Shoham; Yehuda Benayahu; Omri Bronstein; Micha Ilan; Tom Shlesinger; Jonathan Belmaker (Coral Reefs, 2026)
Depth plays a crucial role in shaping marine biodiversity patterns, with species richness typically decreasing with depth. Despite extensive documentation of this pattern, the drivers of richness changes across depth remain unclear. Richness–depth patterns can arise from multiple proximate mechanisms acting simultaneously, such as changes in abundance, evenness, and the spatial aggregations of individuals. Using a unified framework, we examined variation in richness patterns and their underlying mechanisms in the northern Red Sea for fishes (down to ~ 150 m), Scleractinia, Octocorallia, and Porifera (down to ~ 45–70 m). Our results reveal taxa-specific richness responses. Overall, abundance changes emerged as the most consistent driver of richness variation with depth, although its direction and magnitude differed among taxa. Fish richness declined with depth, primarily driven by reduced abundance and lower evenness. In contrast, Porifera exhibited increased richness with depth, largely explained by higher abundances. Scleractinia richness peaked at 10 m and slowly declined with depth, similarly linked to changes in abundance. In contrast, Octocorallia showed a slight richness increase with depth, mainly due to higher evenness at greater depths, although gaps in observations at intermediate depths may have obscured fine-scale peaks within the studied range. Increasing sampling scale (by combining sampling units) amplified these patterns. The results highlight the importance of understanding abundance gradients for richness, which may be overlooked when relying solely on cover-based estimates. The taxon-specific variability in richness–depth patterns challenges the conventional expectation of declining richness with depth, yet uncovers important commonality in the underlying mechanisms.

Refugia, but Not for Everyone: Genetic Structure Differentiates Shallow and Mesophotic Populations of the Brooder Sponge Ircinia variabilis - Tom Morav; Micha Ilan; Liron Goren; Tal Idan; Sigal Shefer; Yaron Tikochinski; Julio A. Díaz; Giorgos Chatzigeorgiou; Carlota Gracia‐Sancha; Ana Riesgo; Sergi Taboada (Molecular Ecology, 2026)
Understanding how gene‐flow and selection interact across environmental gradients is essential for assessing population resilience and evaluating the deep‐refugia potential of mesophotic habitats under rapid climate change. In the context of depth, genetic connectivity patterns have been documented for broadcast‐spawning species, but that of brooding marine invertebrates remains largely unexplored, leaving the role of mesophotic habitats as potential refugia uncertain. Here, we investigated the genetic structure of the brooder sponge Ircinia variabilis across shallow and mesophotic habitats in the Eastern Mediterranean and across shallow sites spanning multiple Mediterranean basins (i.e., Mallorca, Ionian‐Sea and Israel). By quantifying depth and distance‐related connectivity, and assessing the relative roles of neutral processes and temperature‐driven selection, we evaluated the genetic connectivity of I. variabilis and the potential of mesophotic habitats to function as refugia. Using ddRADseq, we obtained 957 SNPs, to characterize gene‐flow patterns, genetic structure, and environmental influences on differentiation. Ircinia variabilis exhibited pronounced vertical and geographic genetic structure, consistent with limited larval dispersal. Notably, Ionian‐Sea populations were genetically closer to Mallorca than to the geographically closer Israeli populations, suggesting influence of oceanographic barriers. Analyses of selection‐associated loci indicate that environmental variability contributes to population divergence, supporting local adaptation. Along the Israeli coast, pronounced differentiation between shallow and mesophotic populations highlights depth as a key axis of evolutionary divergence. Limited vertical connectivity challenges a central assumption of the deep refugia hypothesis, suggesting mesophotic populations may not sustain shallow populations under climate change.

Sponge abundance and diversity patterns in the shallow and mesophotic reefs of the northern Red Sea - Lilach Raijman-Nagar; Liron Goren; Sigal Shefer; Micha Ilan (Frontiers in Marine Science, 2024)
Accumulating data on the increasing degradation of coral reefs worldwide has led to a focus on the unique mesophotic coral ecosystem (MCE) as a potential refuge for threatened shallow-water species (i.e., the deep reef refugia hypothesis: DRRH). Sponges play a crucial role in coral-reef functioning but are often overlooked in benthic surveys. This knowledge gap is especially true for the Red Sea, where data on sponge abundance, coverage and species composition are scarce. Furthermore, to date, no study has examined mesophotic sponges in the Red Sea. Here we compared sponge abundance and diversity metrics between shallow and mesophotic reefs at two sites in the Gulf of Aqaba, northern Red Sea. We also examined the role of biotic and abiotic parameters in determining sponge variability between sites and depths. Sponge diversity metrics significantly varied with increasing depth and between sites. Sponge species composition also differed significantly between depth and sites. However, parameters measured in the water column, that is, Total Organic Carbon (TOC), Particulate Organic Carbon (POC), NOx, etc., did not differ between depths and sites, except for Synechococcus and Prochlorococcus concentration, which did. The findings indicated that site characteristics and biotic interactions may play an essential role in determining sponge diversity and community composition. Between-site differences in sponge fauna revealed in the study highlight the importance of considering the variability in the benthic communities and the factors controlling it when designing management tools for coral reefs, particularly for the northern Red Sea.

High variability and enhanced nocturnal oxygen uptake in coral reef sponges - Raz Moskovich; Rei Diga; Micha Ilan; Gitai Yahel (Limnology and Oceanography, 2023)
Sponges are animals that feed by filtering water through their perforated body. We examined the in situ diel dynamics of sponge metabolism by continuously measuring the oxygen concentrations in the water inhaled and exhaled by undisturbed sponges. A clear daily pattern of oxygen removal was evident for six of the seven species we studied with their nocturnal oxygen removal being almost double the diurnal values (+ 86 ± 57%). Oxygenic photosynthesis by the sponge's symbiotic or endolithic phototrophic microbes may explain some of the diel difference, but significant day–night differences were also observed in three sponge species for which no evidence of photosynthetic activity (tested with imaging pulse‐amplitude‐modulation Fluorometry) was found. Mean oxygen removal (± 95% confidence interval for the mean) per species ranged from 1.7 ± 1 μ mol O 2 per liter (hereafter: μ mol O 2 L −1 ) for the low microbial abundance (LMA) sponge Callyspongia siphonella to 30.5 ± 10.5 μ mol O 2 L −1 for the high microbial abundance HMA) sponge Theonella swinhoei with considerable variation in oxygen removal across all scales (minutes to hours, within and among specimens). Events of high oxygen removal (> 50 μ mol L −1 ) were regularly observed for five of the seven species and were predominantly nocturnal, occasionally lasting several hours. The high variability in oxygen removal stresses the need for long‐term in‐situ measurements of benthic suspension feeders metabolism.

A comparison of mesophotic and shallow sponge holobionts resilience to predicted future temperature elevation - Lilach Raijman-Nagar; Liron Goren; Sigal Shefer; Raz Moskovich; Zhiyong Li; Micha Ilan (Frontiers in Marine Science, 2023)
Climate change is predicted to have detrimental impacts on sessile invertebrates, including sponges. Mesophotic ecosystems have been suggested to play a major role as refugia for coral reef sponge species, however knowledge regarding the ability of mesophotic sponges to cope with thermal stress is scarce. In this study we compared the response of the sponge Diacarnus erythraeanus , a widespread Red Sea sponge, from the shallow and mesophotic reef, to moderate and acute temperature elevation (2°C and 6°C, respectively) for short and long term periods (two and 35 days, respectively) by measuring physiological parameters (respiration, oxygen removal, pumping rates, and photosynthetic efficiency), and the microbiome composition change. The results indicated that mesophotic and shallow populations of D. erythraeanus are highly tolerant to both moderate and acute heat stress, demonstrating a high survival rate (100%) across the experimental treatments, with no visible signs of bleaching or necrosis. Exposure to heat stress resulted in significant alterations in the physiological parameters of sponges, including higher respiration rate and lower photosynthetic efficiency. These alterations were accompanied by correspondingly significant microbial adjustments, thus emphasizing the essential role of the microbiome in the host’s ability to persist when facing essential environmental stress. Moreover, while shallow and mesophotic sponges showed similar physiological tolerance to heat stress, their microbial response differed: while the microbiome diversity of the mesophotic sponges remained stable throughout the experiment, the shallow one significantly changed. This result suggests that their underlying coping mechanisms might differ between mesophotic and shallow populations. Since the associated-microbiome is largely regulated by the sponge-host genetics, difference in microbial adjustments to stress between populations, could indicate genetic variability between hosts. Therefore, while the results of this study support the hypothesis that mesophotic coral reefs could serve as thermal refugia for some sponge species, it raises the question regarding the validity of MCEs as a refuge for shallow populations. Finally, it emphasizes the crucial need to elucidate the underlying mechanisms governing the sponge-microbiome interactions, specifically in the context of the anticipated climate change scenarios.

New Negombata species discovered: latrunculin mystery solved - Lilach Raijman-Nagar; Sigal Shefer; Tamar Feldstein-Farkash; Lion Novak; Micha Ilan (Coral Reefs, 2023)

Sponge-Associated Polychaetes: Not a Random Assemblage - Liron Goren; Tal Idan; Sigal Shefer; Micha Ilan (Frontiers in Marine Science, 2021)
Polychaetes are among the most common marine organisms, and in many habitats they dominate both in species richness and abundance. They are often found in association with other organisms. Specifically, sponges with their complex three-dimensional internal architecture, are known to host a great diversity of polychaetes. Due to the fact that a large number of sponge-associated polychaete species are known to be common on other substrates, most studies agree that they represent an opportunistic part of the sponge-inhabiting assemblage, without any selection of species tightly associated with sponges. The current study aimed to shed light on polychaetes affinity to sponges. We applied Clarke and Warwick’s taxonomic distinctness indices and test for random assembly, to a dataset compiled of 13 publications that provided polychaete species lists from massive-sponges across the Mediterranean Sea, and compared them with benthic-polychaete species lists from all of the Mediterranean and its zoogeographical regions. These indices are considered to be independent of sampling efforts and setting, and can be applied on presence/absence data, making it possible to compare data from multiple studies. We further compared the trophic structure of sponge-associated polychaetes between the Mediterranean’s zoogeographical regions. Our results show that the trophic structure of the sponge-associated polychaete community, was found to be stable across the entire Mediterranean Sea. Moreover, randomization tests showed that at almost all observational scales (e.g., study, region, Mediterranean) the phylogenetic diversity is not assembled at random, and that sponge-associated polychaete communities are composed of taxonomically related species. These results support the statement that polychaete assemblages inhabiting sponges are not a transient facultative assembly of species, but rather stable, diverse and specialized communities which are well adapted for life in this habitat.

New discoveries in Eastern Mediterranean mesophotic sponge grounds: updated checklist and description of three novel sponge species - TAL IDAN; SIGAL SHEFER; TAMAR FELDSTEIN; MICHA ILAN (Mediterranean Marine Science, 2021)
Rich and diverse mesophotic sponge grounds were recently discovered along the easternmost part of the Mediterranean Sea (Israeli coast). Six sites have been surveyed over the last decade (2009-2019) and the sponge specimens discovered and collected in these expeditions have increased the known sponge richness of the Israeli fauna by ~34%. Here we provide an updated checklist along with the distribution of the various species in seven mesophotic sponge grounds along the coast. Nine mesophotic species have been added, seven of which are new to the Israeli coast. Moreover, we describe three novel species: Hemiasterella verai sp. nov., Axinella venusta sp. nov., and Plakortis mesophotica sp. nov. H. verai sp. nov. differs from other congeneric species in both shape and color; in addition, it has thinner megascleres with more abundant oxeas and microscleres containing both oxyasters and strongylasters. A. venusta sp. nov. is a rather stiff and smooth axinellid with only a few short protruding spicules, and differs from other congeneric species mainly in shape and color. P. mesophotica sp. nov. is characterized by many folds and grooves, and molecular analysis revealed only a 96% similarity with Plakorits simplex.The discovery of these novel species highlights the importance of studying ecosystems that are not readily accessible. Further research of these mesophotic sponge grounds is needed in order to establish the community baseline data and support conservation attempts for these unique habitats.

Macrofauna Inhabiting Massive Demosponges From Shallow and Mesophotic Habitats Along the Israeli Mediterranean Coast - Liron Goren; Tal Idan; Sigal Shefer; Micha Ilan (Frontiers in Marine Science, 2021)
Sponges have long been considered as “living hotels” due to the great diversity and abundance of other taxonomic groups often found in association with them. Sponges are the dominant components of benthic communities in the Levant Sea; and especially in the recently discovered mesophotic sponge grounds off the coast of Israel. However, almost no data exist regarding their associated macrofauna. The current study sought to identify the macrofauna associated with massive sponges along the Israeli Mediterranean coast; and to compare the role of sponges, as ecosystem engineers, or “living hotels,” in both the shallow-water and mesophotic habitats. Sixty-four massive sponge specimens, from 10 different species, were collected from shallow and mesophotic habitats by SCUBA diving and Remotely Operated Vehicle, respectively. Sponge volume was estimated, specimens were dissected, and the associated macrofauna were identified. Our results reveal that the sponges supported a diverse assemblage of associated macrofauna. A total of 61 associated taxa were found, including species reported for the first time in Israel. A clear, differentiation existed in the structure of the associated assemblage between the two habitats, which is mainly attributed to four species (two polychaetes, a crustacean, and a brittle star). The trophic composition remained stable across the two habitats. No correlation was found between sponge volume and the associated fauna community parameters. The highest richness of associated fauna was found in the mesophotic habitat, where sponge diversity is also higher. In contrast, a greater endobiont abundance and density were recorded in the shallow habitat, where massive sponges may be a limiting factor due to their lower richness and abundance. Our findings emphasize the importance of sponges as ecosystem engineers, and suggest that sponge diversity may be an important factor that contribute to benthic biodiversity in these regions.

Sponges in a Changing Climate: Survival of Agelas oroides in a Warming Mediterranean Sea - Tal Idan; Liron Goren; Sigal Shefer; Micha Ilan (Frontiers in Marine Science, 2020)
Sponges hold a key role in benthic environments, and specifically in the Mediterranean Sea. Past events of mass mortality in sponge communities have been linked to extended periods of high-temperature anomalies, yet it is unknown how a gradual change, such as the constant rise in global seawater temperatures, will affect biodiversity. Here we present a case study of Agelas oroides , a common massive sponge in the Mediterranean Sea, found at a wide depth range of 1–150 m. Last documented in the 1970s, A. oroides was considered lost from the Israeli coastal fauna. However, its recent rediscovery in mesophotic depths, where environmental conditions are stable, provided an opportunity to examine whether it can survive the present conditions in the shallow Israeli coast – where temperatures increased by 3°C during the past 60 years, while the nutrients concentration decreased following the damming of the Nile River. To test this hypothesis, A. oroides individuals were collected during winter from mesophotic sponge grounds (100–120 m) and transplanted to a shallow rocky habitat (10 m). Control individuals were transplanted back to the mesophotic habitat. Sponge survival, temperature, and nutrient concentrations were measured in both habitats. The shallow-transplanted sponges’ survival decreased only when the ambient temperature exceeded 28°C. In contrast, the control group at the mesophotic depth, where the temperature never rose above 20°C, survived the duration of the experiment. Our findings suggest that a prolonged period of high temperatures may constitute a major factor in A. oroides survival and disappearance from the Israeli shallow habitats.

Does Depth Matter? Reproduction Pattern Plasticity in Two Common Sponge Species Found in Both Mesophotic and Shallow Waters - Tal Idan; Liron Goren; Sigal Shefer; Itzchak Brickner; Micha Ilan (Frontiers in Marine Science, 2020)
Determining demosponge reproductive strategies is essential to understanding their ecology and life history, as well as for the management of benthic marine environments. This is especially important in mesophotic ecosystems, which have been suggested to serve as a refuge for shallow-water populations and for which knowledge is lacking. Here we compared the reproductive strategies of two common Mediterranean demosponges species: Chondrosia reniformis and Axinella polypoides , which can be found in both shallow and mesophotic habitats along the Israeli coast. Samples were collected over 2 years, via SCUBA diving from the shallow coast (2–32 m) and Remotely Operated Vehicle from the mesophotic sponge grounds (95–120 m). A. polypoides and C. renifornis differed in oocyte morphology and development, but both demonstrated reproductive plasticity with regard to temperature and depth: temperature appears to regulate their reproduction in the shallow water, as both species exhibited seasonality; whereas, in the mesophotic zone, where the temperature amplitude is much smaller, seasonality was not observed for either species. Furthermore, in the mesophotic zone, C. reniformis exhibited low fecundity and probably invests more in asexual reproduction by budding. Mesophotic A. polypoides , in contrast, exhibited enhanced and continuous asynchronous sexual reproduction year-round. Our findings suggest that reproduction plasticity may be a general rule for sponge species that inhabit different habitats; such plasticity could allow sponges to thrive in different environmental conditions. These findings further emphasize the importance of protecting the mesophotic sponge grounds, which can serve as a refuge in the face of the adverse impact of anthropogenic disturbances and rising seawater temperatures.

Schizoporella errata (Bryozoa, Cheilostomata) in the Mediterranean Sea: abundance, growth rate, and reproductive strategy - Noga Sokolover; Andrew N. Ostrovsky; Micha Ilan (Marine Biology Research, 2018)

Shedding light on an East-Mediterranean mesophotic sponge ground community and the regional sponge fauna - TAL IDAN; SIGAL SHEFER; TAMAR FELDSTEIN; RUTH YAHEL; DOROTHEE HUCHON; MICHA ILAN (Mediterranean Marine Science, 2018)
Sponges are a diverse and abundant phylum, globally inhabiting many hard-bottom habitats. However, data on the East-Mediterranean sponge communities are scarce, outdated, and limited to the shallow waters. This study sought to expand the knowledge of the poriferan fauna along the Mediterranean shore of Israel. A newly-discovered mesophotic sponge ground at ~100 m depth was studied using a remotely-operated vehicle (ROV), in addition to shallow-water surveys conducted by scuba diving. In the mesophotic ecosystem, sponges, serving as environmental engineers, create complex 3D structures that attract invertebrates and fish. The results of the quantitative survey of this mesophotic sponge ground reveal that it maintains a rich and diverse community with an estimated 63 species, and a high sponge percent coverage (~35%). Several of the mesophotic species are documented for the first time from the Levant basin, while others might be novel species. Here we identified over 100 sponge species along the Mediterranean coast of Israel, 33 of which were sampled from the mesophotic sponge ground. The updated sponge list supports the hypothesis that the Levantine sponge diversity is not as species-poor, compared to other parts of the Mediterranean Sea, as has previously been considered. In addition, shallow and mesophotic sponge community compositions were found to only partially overlap. Moreover, the latter harbors some species that have disappeared from the shallow habitats, and only a few species thrive along the entire depth range. We suggest that mesophotic sponge grounds may serve as refugia for species stressed by the rising temperatures in shallow waters and should be protected from anthropogenic influences such as oil and gas drilling.

A novel Chromatiales bacterium is a potential sulfide oxidizer in multiple orders of marine sponges - Adi Lavy; Ray Keren; Ke Yu; Brian C. Thomas; Lisa Alvarez‐Cohen; Jillian F. Banfield; Micha Ilan (Environmental Microbiology, 2018)
Summary Sponges are benthic filter feeders that play pivotal roles in coupling benthic‐pelagic processes in the oceans that involve transformation of dissolved and particulate organic carbon and nitrogen into biomass. While the contribution of sponge holobionts to the nitrogen cycle has been recognized in past years, their importance in the sulfur cycle, both oceanic and physiological, has only recently gained attention. Sponges in general, and Theonella swinhoei in particular, harbour a multitude of associated microorganisms that could affect sulfur cycling within the holobiont. We reconstructed the genome of a Chromatiales (class Gammaproteobacteria) bacterium from a metagenomic sequence dataset of a T. swinhoei ‐associated microbial community. This relatively abundant bacterium has the metabolic capability to oxidize sulfide yet displays reduced metabolic potential suggestive of its lifestyle as an obligatory symbiont. This bacterium was detected in multiple sponge orders, according to similarities in key genes such as 16S rRNA and polyketide synthase genes. Due to its sulfide oxidation metabolism and occurrence in many members of the Porifera phylum, we suggest naming the newly described taxon Candidatus Porisulfidus .

Intermittent Hypoxia and Prolonged Suboxia Measured In situ in a Marine Sponge - Adi Lavy; Ray Keren; Gitai Yahel; Micha Ilan (Frontiers in Marine Science, 2016)

Barnacle fouling in the M editerranean sponges A xinella polypoides and A xinella verrucosa - Markus Haber; Amir Gur; Daniela Blihoghe; Micha Ilan (Marine Ecology, 2013)
Secondary metabolites protect many marine sponges ( P hylum: P orifera) from settlement by fouling organisms. Previous studies on the subtidal demosponge A xinella verrucosa collected in the W estern M editerranean led to the isolation of compounds that inhibited the settlement of cyprids larvae of the intertidal barnacle B alanus amphitrite , and the enzyme chitinase, which plays a key role in the molting cycle of crustaceans. However, in a field survey conducted at three locations in I srael, E astern M editerranean S ea, we observed that A . verrucosa is fouled by the subtidal barnacle B alanus trigonus , a previously unknown association. Settlement inhibition assays using B . amphitrite with chemical extracts from I sraeli A . verrucosa and A xinella polypoides , a sympatric, congeneric sponge that seems not to be fouled by B . trigonus , showed that cyprid larvae of B . amphitrite were inhibited by the extracts of both sponges from settlement at concentrations several magnitudes lower than natural volumetric extract concentration in the sponges. These results indicate that, unlike the intertidal barnacle B . amphitrite , the subtidal B . trigonus is unaffected by the compounds from A . verrucosa , stressing and underlining the importance of using suitable target organisms ( i.e . from the same habitat) to test for ecologically relevant antifouling activities.

Marine-Based Cultivation of Diacarnus Sponges and the Bacterial Community Composition of Wild and Maricultured Sponges and Their Larvae - Oded Bergman; Markus Haber; Boaz Mayzel; Matthew A. Anderson; Muki Shpigel; Russell T. Hill; Micha Ilan (Marine Biotechnology, 2011)

Differential Gene Expression in a Marine Sponge in Relation to Its Symbiotic State - Laura Steindler; Silvia Schuster; Micha Ilan; Adi Avni; Carlo Cerrano; Sven Beer (Marine Biotechnology, 2007)

Chemical warfare on coral reefs: Sponge metabolites differentially affect coral symbiosis in situ - Joseph R. Pawlik; Laura Steindler; Timothy P. Henkel; Sven Beer; Micha Ilan (Limnology and Oceanography, 2007)
Coral reef ecosystems are characterized by high species diversity and intense levels of biotic interaction, particularly competition for space among sessile benthic invertebrates. Using in situ pulse amplitude modulated fluorometry, we demonstrate that secondary metabolites present in the tissues of some Caribbean sponge species have rapid allelopathic effects on the symbiotic algae (zooxanthellae) that live in coral tissues and provide the energy for coral growth and reef formation. When incorporated into stable gels at natural concentrations and placed in contact with brain coral heads on shallow reefs for ~18 h, secondary metabolites of some sponge species caused a decrease in the photosynthetic potential of the symbiotic algae and bleaching of the coral tissue, whereas those of others interfered with algal photosynthesis without causing bleaching. Some sponges produce metabolites with different modes of action for competing with reef corals.

Transmission, plasticity and the molecular identification of cyanobacterial symbionts in the Red Sea sponge Diacarnus erythraenus - Matan Oren; Laura Steindler; Micha Ilan (Marine Biology, 2005)

The hydrozoan coral Millepora dichotoma : speciation or phenotypic plasticity? - Efrat Meroz-Fine; Itzchak Brickner; Yossi Loya; Micha Ilan (Marine Biology, 2003)

Further steps in the initiation of cell cultures from embryos and adult sponge colonies - Baruch Rinkevich; Micha Ilan; Ronit Blisko (In Vitro Cellular & Developmental Biology - Animal, 1998)